The Juridical Personality of Companies in Bahraini Law. - Gumed, Prof. Salem A. (IJRDO - Journal of Social Science and Humanities Research, 2018)
Legal personality (also juristic personality and artificial personality) is the characteristic of a non-living entity regarded by law to have the status of personhood. It allows one or more natural persons to act as a single entity (a composite person) for legal purposes. Legal personality, in many jurisdiction, allows that composite to be considered under law separately from its individual members or shareholder. They may sue and be sued, enter contracts, incur debts, and own property. Entities with legal personality may also be subject to certain legal obligations, such as payment of taxes, and may shield their shareholders from personal liability. This study explores the related concepts of corporate legal personality and limited liability In Bahraini Law of Companies, which are central to developing understanding of companies’ law and are essential that one is devised to take time here to absorb these fundamental principles.